Estudo do comportamento de vigas mistas com perfil de alma senoidal - Alexander Galvao Martins (2009)
The corrugated web profiles have been employed in the construction of commercial warehouses, industrial buildings and footbridges as well. Hence, researches have focused on insulated steel profiles behavior, while few references are found about composite structures with corrugated web profile, in particular the sinusoidal geometry. Neither Brazilian standard ABNT NBR 8800: 2008 nor international standards provide procedures for calculation and design of corrugated web steel elements covering all the phenomena involved on its structuralbehavior. Therefore, the aim of this work is to propose procedures for calculating composite beams formed by sinusoidal web steel profile overlapped by massive concrete slab or by decks concreted over steel sheeting, in the regions of sagging and hogging bending moment.In order to achieve that, three tests of composite connections on sinusoidal web profile were performed in the Laboratory of Experimental Analysis of Structures (LAEES), at the School of Engineering, Federal University of Minas Gerais. Data obtained from these tests and alsofrom composite beams with sinusoidal web profiles tests performed by MOTAK & MACHACEK at Czech Technical University in Prague were used to validate finite element numerical models. Finally, these models were used for parametric studies to obtain the bending moment resistance and composite connection fundamental properties as well as in the hogging bending moment region, and bending moment resistance of composite beams in the sagging bending moment region.